Assessment of health and environmental benefits of REACH. Final report (Brussels, 2012)
"The objective of this project is to assess consequences of the current implementation of REACH with regards the expected benefits to human health and the environment. The outcome of the contract will aim at feeding the necessary information into the Commission general report on the experience acquired with the operation of REACH and the 2012 review process in general. Taking the results of the REACH baseline study as a starting point, the contractor will review the methodology to assess the health and environmental benefits of REACH used in the Extended Impact Assessment with a view to providing more precision in the assessment of these impacts. The project's results should ensure that the health and environmental benefits are well understood and presented in a way that could be traceable if changes to the Regulation are proposed. The project will also result in suggesting possible improvements to the implementation of REACH and possibly specific provisions of REACH which could lead to an increase in the effectiveness of REACH in ensuring high level of protection of human health and the environment."